Paternalistic leadership and team performance in China teaching hospitals: Examining roles of team psychological safety and team empowerment - Chong, Yatkeung (2013)
People and hospitals are pressured to improve department performance; leader management is crucial in promoting performance in a fast changing and competitive situation. Department leaders in Chinese teaching hospitals are both academic leaders and tutors of the junior and, therefore, act as father. Such father-like leader is called as paternalistic leadership rooted in Chinese Confucian culture. This research identifies the influencing processes that underlie the effect of the three dimensions of paternalistic leadership (benevolent, moral, authoritarian) on the performance of departments in Chinese teaching hospitals. Based on data collected in 15 teaching hospitals in Guangzhou, Chengdu, Shanghai, and Beijing, the results showed that team psychological safety and team empowerment sequentially mediated the effects of benevolent leadership and moral leadership on team performance. However, it was found that authoritarian leadership had no effect on team psychological safety. Selfless benefactor and authentic PL types, that both are characterized with high benevolence and morality, had the highest scores on team psychological safety and team empowerment. The laissez-faire and dictatorial PL types, that both are characterized with low benevolence and morality, were found in a large proportion of departments and had the lowest scores on team psychological safety, team empowerment, and team performance. The results emphasized the importance of practicing benevolent leadership and moral leadership in Chinese teaching hospitals and future research is needed on paternalistic leadership, team psychological safety, team empowerment and team performance relationship in other contexts. Moreover, it is also important to study other effects and influences of paternalistic leadership dimensionality and authoritarian leadership.